PENGARUH NORMA SUBJEKTIF, MOTIVASI INVESTASI, PENGETAHUAN INVESTASI, PERSEPSI RETURN DAN LITERASI KEUANGAN TERHADAP MINAT MAHASISWA BERINVESTASI SAHAM DI PASAR MODAL (Studi Empiris Pada Mahasiswa Akuntansi FEB UNISMA dan UNIBRAW di Malang) - Ernia Taufiqoh; Nur Diana; Junaidi Junaidi (Universitas Islam Malang, 2019)
ABSTRACT This study aims to determine the effect of subjective norms, investment motivation, investment knowledge, perceptions of return and financial literacy on the interest of students investing in capital markets in accounting students undergraduate programs in Malang. Viewed from previous studies that were inconsistent with the results, so this motivated the writer to re-examine the research. The population is active students of the 2016 class of Accounting majoring in the Faculty of Economics and Business, Islamic University of Malang and Brawijaya University, and the sample used is 83 respondents. This data collection is done through a questionnaire. The data analysis in this research uses SPSS version 16. This sampling technique uses purposive sampling method and data testing techniques used in this study include descriptive tests, validity, reliability, normality tests, classic assumption tests and multiple linear regression analysis . The results of the analysis show that: subjective norms, investment motivation, perceptions of returns have a significant effect on students' interest in investing in the stock market, while investment knowledge and financial literacy have no significant effect on the interest in stock investment in the capital market. Keywords: Investment Interest, Subjective Norms, Investment Motivation, Investment Knowledge, Perception Return, Financial Literacy.